Условия безопасного торможения бесконтактных двигателей с постоянными магнитами без использования специальных тормозных устройств - Акинин, Константин Павлович (НТУ "ХПИ", 2013)
The subject of this paper is the braking method of permanent magnet brushless motors equipped with two-stage frequency converter without special brake devices. The braking power dissipates in motor windings by the stator currents increase. Safe braking conditions of permanent magnet brushless motors are given.
Keywords: регулируемый электропривод; электродвигатели переменного тока; тормозные режимы; преобразователи частоты; тормозной резистор; высокоскоростные БДПМ